The Effectiveness Investigation of New Retrofitting Techniques for RC Frame against Progressive Collapse - MohsenAli Shayanfar; Mohammad Bigonah; Danial Sobhani; Masoud Zabihi-Samani (Civil Engineering Journal, 2018)
Progressive collapse in a building has caused local and subsequent damage throughout the system to spread and large-scale causes the collapse of the entire building. Progressive collapse is usually due to fire, gas explosion, terrorist attack, vehicle collisions, misplaced design and construction. Therefore, it is necessary to study the iMPact of this phenomenon and rebuild the building against it. Based on this, in this research, we will examine and evaluate practical solutions for reinforcing reinforced concrete frames against progressive collapse. The proposed solutions in this study were the use of reinforcing bars at the top and bottom of the beam, the effect of the layout of the cross section reinforcement for the participation in the chain performance, the use of Carbon Fiber Reinforced Polymer (CFRP) sheet at the bottom and three sides of the beam and the effect of the additional layer of CFRP sheet in the section performance of the beam against progressive collapse. In this study, a 2-story frame is modeled using OpenSees software and retrofitted with the above techniques, and the effectiveness of each of these techniques is evaluated in the final performance. The results show that the best approach to reinforcing the beam is by rebar and CFRP, which has resulted in improved chain performance and the greatest reduction of vertical displacement in the beam.